Migraine, hormones and the menopausal transition. (4th May 2018) - Hipolito Rodrigues, M. A.; Maitrot-Mantelet, L.; Plu-Bureau, G.; Gompel, A.
Abstract: Migraine is a common, disabling and incapacitating headache disorder that may be triggered by many factors, such as hormones especially during the perimenopausal period, where large alterations in estradiol levels can occur. The evidence implies that hormonal fluctuations are one of the important triggers of migraine. During reproductive life and during hormonal contraception, the course of migraine can be impacted. Different types of migraine with and without aura can be variously influenced by hormones. Migraine can constitute a risk factor for stroke and this must be taken in account for menopause hormone therapy. Hormone therapy is a possible approach to prevent migraine that happens during the menopause transition. Scarce data on the various regimens and types of hormone therapy are available. Transdermal estradiol displays a more favorable profile on migraine than oral estrogens because it may provide more constant levels of estrogens.